2016
DOI: 10.1007/s11356-016-7665-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of phytogenic feed additives to substitute in-feed antibiotics on growth traits and blood biochemical parameters in broiler chicks challenged with Salmonella typhimurium

Abstract: There is a growing concern over the use of antibiotics due to the increased resistance of pathogens in broiler. The present study was designed to find the comparative effect of an antibiotic, and some phytogenic on performance traits, blood biochemical parameters, and antioxidant status during starter phase exposed to Salmonella typhimurium challenge. A total of 560-day-old broiler chicks (Ross 308) were randomly allocated to seven treatments (eight replicates). Control (basal diet); T1, infected with Salmonel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
55
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 26 publications
7
55
1
Order By: Relevance
“…In addition, the essential oils and phytobiotics (carvacrol from oregano, cinnamaldehyde from cinnamon and capsaicin) performed similar to the control group showing the effectiveness since the birds in the treatments were infected. An improved growth performance with phytobiotics without any bacterial infection (Buchanan et al 2008;Ahmad et al 2011;Lee et al 2015) and with a bacterial infection (Abudabos et al 2016) have been reported previously. The improved performance, gut physiology and blood biochemical profile may be due to the mechanism of action of essential oils supplemented in the current study.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…In addition, the essential oils and phytobiotics (carvacrol from oregano, cinnamaldehyde from cinnamon and capsaicin) performed similar to the control group showing the effectiveness since the birds in the treatments were infected. An improved growth performance with phytobiotics without any bacterial infection (Buchanan et al 2008;Ahmad et al 2011;Lee et al 2015) and with a bacterial infection (Abudabos et al 2016) have been reported previously. The improved performance, gut physiology and blood biochemical profile may be due to the mechanism of action of essential oils supplemented in the current study.…”
Section: Discussionmentioning
confidence: 69%
“…On day 30, 1 cm section of the lower ileum from two birds per replicate was prepared as described by Abudabos et al (2016). Measurements of height and width of the villi were based on at least 10 well-oriented villi per section using a microscope (IX71 Inverted Olympus).…”
Section: Intestinal Histologymentioning
confidence: 99%
See 1 more Smart Citation
“…The body produces free radicals continuously for the need of normal physiological functions, but their excessive level may cause damage to the plasma membrane and organelles (Khan et al 2011). Nutritional approaches are considered to lessen the undesirable effects of heat stress by maintaining feed intake, water and electrolyte balance or by the supplementation of antioxidant vitamins, essential oils, minerals and natural herbs (Khan et al 2011;Rahman et al 2014a;Majid et al 2015;Abudabos et al 2016;Chand et al 2017). Supplementation of diets with natural antioxidants is a favourable strategy to decrease the lethal effects of heat stress in birds (Chand et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In order to find effective substitutes to antibiotic growth promoters, several aromatic plants have been evaluated in poultry industry (Abudabos, Alyemni, Dafallah, & Khan, ; Khan, Naz, Nikousefat, Tufarelli, & Laudadio, ). These herbs, or their extract, show significant antimicrobial, antifungal, antioxidant, and physiological modulation proprieties (Ardalan, Omid, Golnaz, & Mahdi, ; Çabuk, Eratak, Alçicek, & Bozkurt, ; Jang, Ko, Kang, & Lee, ).…”
Section: Introductionmentioning
confidence: 99%